The effectiveness of antimicrobial preservatives testing of the medicine "Efial" - Borshchevskiy, G; Railko, Z; Reida, V (Annals of Mechnikov’s Institute, 2020)
Dosage form - spray is one of the most advanced and modern methods of medicines administration in the human body. The advantage of airborne mode of medicines delivery (inhalation) than injection and enterable methods is the ability to direct and rapid impact on the area of inflammation of the mucous membranes or when fine evaporation - on the bronchi and lungs. When finished medicinal product itself has not a sufficient antimicrobial activity, in its composition can be administered antimicrobial preservatives, which is especially important for medicines as aqueous solutions. Because microbial contamination can cause infection of the patient or damage to the finished product, antimicrobial preservatives are designed to prevent microbial contamination of the finished medicinal product during storage and use, especially in the case of multi-container packaging. Rationale of composition and technology of spray “Efial” was conducted by us using physical, chemical and technological methods. An important task in creating new medicines is the study of preservatives choice. The aim of this work is to test the effectiveness of antimicrobial preservatives of spray “Efial”. Material & methods The object of the test – “Efial”containing preservatives on the lower: series 10814 (holding inoculated samples at a temperature of 20-25 º C) and series 10914 (holding inoculated samples at 2-8 º C). Materials: 1. Nutrient medium: soy-casein agar, sabouro-dextrose agar. 2. Solutions: buffer solution of sodium chloride and peptone pH =7.0, containing 50 g/l of polysorbate-80, 5 g/l of lecithin, 1 g/l of histidine hydrochloride. Test-microorganisms: Staphylococcus aureus ATCC 6538; Pseudomonas aeruginosa ATCC 9027; Candida albicans ATCC 10231; Aspergillus brasiliensis АТСС 16404. Preparation of inoculums was carried by State Pharmacopoeia of Ukraine, p. 5.1.3. Results & discussion The checks of methods for determining total viable microorganisms suitability have been carried out. It was proved that the method of surface sowing on cups of 1 ml of medicine’s dilution 1:10 is suitable for determining the number of microorganisms in 1 ml and can be used during the test effectiveness of antimicrobial preservatives. Further tests of efficacy of antimicrobial preservatives in the product “Efial”: s. 10 814 (holding inoculated samples at a temperature of 20-25 °C) and s. 10914 (holding inoculated samples at 2-8 °C) were conducted. The test results showed that in storage of the inoculated medicine’s samples at 2-8 °C, there is no significant change in the number of viable cells of the test microorganisms as compared to the original number: • it is marked a tendency to a slight decrease in the number of viable test microorganism Pseudomonas aeruginosa and Staphylococcus aureus on day 7 and 14 that do not meet the admissibility of the effectiveness of antimicrobial preservative according criteria A and B; • it is marked a tendency to a slight decrease in the number of viable test microorganisms Candida albicans and small increase in the number of viable test microorganisms Aspergillus brasiliensis on day 14 that do not meet the admissibility of the effectiveness of antimicrobial preservative according criteria A and B. At the same time, medicine’s samples during storage at 2-8 °C, they are not an increase in the number of microorganisms within 28 days. Conclusions 1. Testing the effectiveness of antimicrobial preservatives (sodium salt propylparahydroxybenzoate - 0.18 mg / ml sodium meathylparahydroxybenzoate - 1.62 mg / ml) in sprays "Efial." It is proved that the chosen preservatives ensure microbiological purity of the drug during storage at 2 to 8 ° C. 2. To ensure proper microbiological purity of the drug during its use after opening the primary packaging, the following measures: • introduced filtration through a filter with a pore size of 0.22 microns, which provides a necessary degree of microbiological purity of the drug; • set the storage mode at 2 to 8 ° C - which is not the reproduction of microorganisms in the sample; • limited term use of the drug after opening - up to 7 days.